Pengaruh Variasi Produk, Online Customer Review, Sosial Media Marketing terhadap Keputusan Pembelian pada Ayam Geprek Jon - Devy Savia Ananta; Misti Hariasih; Rizky Eka Febriansah (Ekonomis: Journal of Economics and Business, 2026)
This study aims to determine the influence of product variety, online customer reviews, and social media marketing on purchasing decisions for Ayam Geprek Jon products in the Sidoarjo region. This study uses a descriptive method with a quantitative approach. The research sample consisted of 100 respondents selected purposively, namely those domiciled in Sidoarjo City, active Instagram users, and have purchased Geprek Jon products. Data were obtained through a questionnaire that measured the indicators of each variable, then analyzed using the Partial Least Square Structural Equation Modeling (PLS-SEM) technique with SmartPLS 3.0 software. The results show that product variety makes it easier for consumers to choose products according to their tastes and needs. Online customer reviews play an important role in providing information and increasing potential buyers' trust in the product. Meanwhile, social media marketing is effective as an interactive communication tool that attracts consumers' attention and builds closeness with the brand.